2017
DOI: 10.1080/09513590.2017.1381837
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of deep infiltrating endometriosis: review of existing options

Abstract: Endometriosis with its estimated incidence rate of ∼7-10% of women of reproductive age is a disease with the wide spectrum of symptoms depending on form and localization of endometrial foci. One clinical form of endometriosis is deep infiltrating endometriosis (DIE), most difficult to manage and generating a lot of direct and indirect treatment costs. We search the literature from PubMed database to establish the role of conservative treatment of DIE. Randomised controlled trials are lacking but in experts opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…[ 3 ] It greatly reduces the quality of life of patients, meanwhile it increases the difficulty of treatment and increases the financial burden of their families. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] It greatly reduces the quality of life of patients, meanwhile it increases the difficulty of treatment and increases the financial burden of their families. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…20 However, whether surgery is the best therapeutic option strongly depends on the experience of the attending surgeon and the probability of being able to achieve total excision of DIE foci. 10 A previous report suggested that conservative surgery should be offered if the total excision of DIE foci is possible. 10 Regarding the alleviation of pain, the benefits of surgery should always be balanced with the risk of intraoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…10 A previous report suggested that conservative surgery should be offered if the total excision of DIE foci is possible. 10 Regarding the alleviation of pain, the benefits of surgery should always be balanced with the risk of intraoperative complications. 21,22 For infertile women with DIE, whether to opt for in vitro fertilization (IVF) treatment or surgery first can be a dilemma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations